DETECTING VOLCANIC ERUPTION PRECURSORS: A NEW METHOD USING GRAVITY AND DEFORMATION MEASUREMENTS - Williams-Jones G.; Rymer H. (My University, 2002)
One of the fundamental questions in modern volcanology is the manner in which a volcanic eruption is triggered; the intrusion of fresh magma into a reservoir is thought to be a key component. The amount by which previously ponded reservoir magma interacts with a newly intruded magma will determine the nature and rate of eruption as well as the chemistry of erupted lavas and shallow dykes. The physics of this interaction can be investigated through a conventional monitoring procedure that incorporates the simple and much used Mogi model relating ground deformation (most simply represented by Δh) to changes in volume of a magma reservoir. Gravity changes (Δg) combined with ground deformation provide information on magma reservoir mass changes. Our models predict how, during inflation, the observed Δg/Δh gradient will evolve as a volcano develops from a state of dormancy through unrest into a state of explosive activity. Calderas in a state of unrest and large composite volcanoes are the targets for the methods proposed here and are exemplified by Campi Flegrei, Rabaul, Krafla, and Long Valley. We show here how the simultaneous measurement of deformation and gravity at only a few key stations can identify important precursory processes within a magma reservoir prior to the onset of more conventional eruption precursors.
Keywords: VOLCANO; MAGMA PHYSICS; MICROGRAVITY; DEFORMATION; CALDERA; ERUPTION TRIGGERS